2023
DOI: 10.1364/oe.488528
|View full text |Cite
|
Sign up to set email alerts
|

Tuning spin-orbit coupling and realizing inverse persistent spin helix by an extra above-barrier radiation in a GaAs/Al0.3Ga0.7As heterostructure

Abstract: A persistent spin helix with equal strength of the Rashba and Dresselhaus spin-orbit coupling (SOC) is expected for future spintronic devices due to the suppression of spin relaxation. In this work we investigate the optical tuning of the Rashba and Dresselhaus SOC by monitoring the spin-galvanic effect (SGE) in a GaAs/Al0.3Ga0.7As two dimensional electron gas. An extra control light above the bandgap of the barrier is introduced to tune the SGE excited by a circularly polarized light below the bandgap of GaAs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…140 Notably, optical tuning is a non-destructive as well as reversible technique that can accurately alter the electron density and effectively screen the intrinsic electric field in the system without relying on the excitation beam. 141 Ma et al 142 investigated the optical tuning of RSOC and Dresselhaus effect in the 2DEG of GaAs/Al 0:3 Ga 0:7 As by measuring the spin-galvanic effect (SGE). They introduced an additional control light above the barrier's bandgap to tune the SGE excited by a circularly polarized light below the bandgap of GaAs.…”
Section: G Optical Manipulation Of Rashba Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…140 Notably, optical tuning is a non-destructive as well as reversible technique that can accurately alter the electron density and effectively screen the intrinsic electric field in the system without relying on the excitation beam. 141 Ma et al 142 investigated the optical tuning of RSOC and Dresselhaus effect in the 2DEG of GaAs/Al 0:3 Ga 0:7 As by measuring the spin-galvanic effect (SGE). They introduced an additional control light above the barrier's bandgap to tune the SGE excited by a circularly polarized light below the bandgap of GaAs.…”
Section: G Optical Manipulation Of Rashba Effectmentioning
confidence: 99%
“…This emphasizes the potential of optical tuning as an effective technique for modulating SOC, offering implications for the design of spintronic devices with prolonged spin coherence time. 142 On the other hand, Michiardi et al, 143 as part of their study on topological insulator Bi 2 Se 3 , demonstrated efficient tuning of RSOC using optical pulses with a picosecond timescale. According to their proposed mechanism, optical excitation above the energy gap induces charge redistribution perpendicular to the surface in the presence of a band-bending surface potential.…”
Section: G Optical Manipulation Of Rashba Effectmentioning
confidence: 99%